THE INNER WORLD OF IMMIGRANT CHARACTERS IN ABDULRAZAK GURNAH’S «BY THE SEA» (International journal of artificial intelligence, 2024)
Abdulrazak Gurnah’s novel «By the Sea» offers a profound exploration of the immigrant experience through its complex characters. This article delves into the inner worlds of these characters, examining how their identities, memories, and emotions are shaped by their journeys. The analysis highlights the psychological and emotional landscapes navigated by the immigrants, reflecting broader themes of displacement, loss, and adaptation.